Analisis Pengetahuan Gizi, Status Gizi, dan Pola Konsumsi Pangan Siswa SD Islam 1 Al Azhar - Zakia Umami; Andi Muh Asrul; Amalina Ratih Puspa (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2021)
School-age children are a population who are at risk of health. According to the Riskesdas 2018, data for school-age children (5-12 years), the prevalence of underweight was 6,8%, obese 9,2%, and stunting was 16,9%. The purpose of this study was to analyze nutritional knowledge, nutritional status, and consumption patterns of students in SD Islam Al Azhar 1. The design of this study was a cross-sectional study conducted at Al Azhar 1 Islamic Elementary School, Jakarta from March to September 2019. Some students who were involved as respondents in this study were 55 people purposive sampling technique. The results showed that children with obesity were 43.3%, normal was 32.7%, overweight was 20%, and underweight was 3.6%. The number of children with good nutrition knowledge was 33 people (60%), adequate nutrition knowledge was 20 people (36,4%), and poor nutrition knowledge was 2 people (3,6%). Average vegetable consumption was 34.57 grams and is classified as less. While the average fruit consumption was 91.88 grams and is classified as adequate. Chi-Square test results showed no correlation between nutritional status with nutritional knowledge and no correlation between nutritional status with consumption of vegetable and fruit.Keyword – Child, Nutritional Knowledge, Consumption Pattern, Nutritional status